Analysis of Demand for International Interns in South Karelia. Case AIESEC. - Koval, Daria (Saimaan ammattikorkeakoulu, 2014)
The objective of the study was to examine the demand for international interns in South Karelian companies. The work was commissioned by AIESEC Saimaa, a student-run organization providing university students with an opportunity to complete a placement period abroad. The commissioned study required performing market research, as well as demand analysis. The main goal of the research was to determine, which local companies and organizations AIESEC Saimaa could contact in the future. The necessary information was gathered from different literature sources, the Internet, statistical data, the case company’s sales database and by interviewing companies in Lappeenranta. The market research was performed by analyzing the research setting with the help of available statistics and other data. The study also includes quantitative analysis of AIESEC’s sales history and qualitative survey research. As a result, this thesis presents both the analysis of the sales database and the demand analysis, which includes opinions and needs of the local companies in regard to employing international interns. The outcomes of the research form solid recommendations for the client company. AIESEC is advised to apply the results in the future while forming a sales strategy and determining target customers.